Brain tissue analysis of impacts to American football helmets. Issue 3 (17th February 2018) - Post, Andrew; Kendall, Marshall; Cournoyer, Janie; Karton, Clara; Oeur, R. Anna; Dawson, Lauren; Hoshizaki, T. Blaine
Abstract: Concussion in American football is a prevalent concern. Research has been conducted examining frequencies, location, and thresholds for concussion from impacts. Little work has been done examining how impact location may affect risk of concussive injury. The purpose of this research was to examine how impact site on the helmet and type of impact, affects the risk of concussive injury as quantified using finite element modelling of the human head and brain. A linear impactor was used to impact a helmeted Hybrid III headform in several locations and using centric and non-centric impact vectors. The resulting dynamic response was used as input for the Wayne State Brain Injury Model to determine the risk of concussive injury by utilizing maximum principal strain as the predictive variable. The results demonstrated that impacts that occur primarily to the side of the head resulted in higher magnitudes of strain in the grey and white matter, as well as the brain stem. Finally, commonly worn American football helmets were used in this research and significant risk of injury was incurred for all impacts. These results suggest that improvements in American football helmets are warranted, in particular for impacts to the side of the helmet.